Not Everyone Wants Roads: Assessing Indigenous People’s Support for Roads in a Globally Important Tiger Conservation Landscape - Clements, Gopalasamy Reuben; Aziz, Sheema Abdul; Bulan, Ramy; Giam, Xingli; Bentrupperbaumer, Joan; Goosem, Miriam; Laurance, Susan; Laurance, William F. (Springer, 2018)
[No abstract available]